Panoramic ultrasound: a novel and valid tool for monitoring change in muscle mass. Issue 3 (3rd January 2017) - Scott, Jessica M.; Martin, David S.; Ploutz‐Snyder, Robert; Matz, Timothy; Caine, Timothy; Downs, Meghan; Hackney, Kyle; Buxton, Roxanne; Ryder, Jeffrey W.; Ploutz‐Snyder, Lori
Abstract: Background: The strong link between reduced muscle mass and morbidity and mortality highlights the urgent need for simple techniques that can monitor change in skeletal muscle cross‐sectional area (CSA). Our objective was to examine the validity of panoramic ultrasound to detect change in quadriceps and gastrocnemius size in comparison with magnetic resonance imaging (MRI) in subjects randomized to 70 days of bed rest (BR) with or without exercise. Methods: Panoramic ultrasound and MRI images of the quadriceps and gastrocnemius muscles were acquired on the right leg of 27 subjects (26 male, 1 female; age: 34.6 ± 7.8 years; body mass: 77.5 ± 10.0 kg; body mass index: 24.2 ± 2.8 kg/m 2 ; height: 179.1 ± 6.9 cm) before (BR‐6), during (BR3, 7, 11, 15, 22, 29, 36, 53, 69), and after (BR+3, +6, +10) BR. Validity of panoramic ultrasound to detect change in muscle CSA was assessed by Bland–Altman plots, Lin's concordance correlation coefficient (CCC), sensitivity, specificity, positive predictive value, and negative predictive value. Results: Six hundred ninety‐eight panoramic ultrasound CSA and 698 MRI CSA measurements were assessed. Concordance between ultrasound and MRI was excellent in the quadriceps (CCC: 0.78; P < 0.0001), whereas there was poor concordance in the gastrocnemius (CCC: 0.37; P < 0.0006). Compared with MRI, panoramic ultrasound demonstrated high accuracy in detecting quadriceps atrophy and hypertrophy (sensitivity: 73.7%; specificity: 74.2%) and gastrocnemius atrophy (sensitivity: 83.1%) and low accuracy in detecting gastrocnemius hypertrophy (specificity: 33.0%). Conclusions: Panoramic ultrasound imaging is a valid tool for monitoring quadriceps muscle atrophy and hypertrophy and for detecting gastrocnemius atrophy.